2015
DOI: 10.1002/cpe.3509
|View full text |Cite
|
Sign up to set email alerts
|

Compiling Vector Pascal to the XeonPhi

Abstract: SUMMARYIntel's Xeon Phi is a highly parallel x86 architecture chip made by Intel. It has a number of novel features which make it a particularly challenging target for the compiler writer. This paper describes the techniques used to port the Glasgow Vector Pascal Compiler (VPC) to this architecture and assess its performance by comparisons of the Xeon Phi with 3 other machines running the same algorithms. Copyright c 0000 John Wiley & Sons, Ltd. Nvidia GPU CONTEXTThis work was done as part of the EU funded CLO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Authors in [11] have identified that the peak performance for the two-pass algorithm occurs at 100 threads. Our initial experiments has verified that considering the range of images from 1152×1152 to 8748×8748, 100 could be our magic number for both OpenMP (optimal number of threads) and GPRM (optimal number of tasks) models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in [11] have identified that the peak performance for the two-pass algorithm occurs at 100 threads. Our initial experiments has verified that considering the range of images from 1152×1152 to 8748×8748, 100 could be our magic number for both OpenMP (optimal number of threads) and GPRM (optimal number of tasks) models.…”
Section: Methodsmentioning
confidence: 99%
“…Authors in [11] explored this further and figured out that the peak performance can be achieved with 100 threads. They have also reported that the performance gap between the Vector Pascal [11] and an optimised OpenMP implementations of the two-pass algorithm with 100 threads is almost 6.4×.…”
Section: Related Workmentioning
confidence: 99%
“…Intel Cilk Plus [21] and OpenCL [22] tools are also available. In other words, one can compile and run source code written for Intel MIC architecture using the Intel ICC compiler unaltered on Intel Xeon processors [23].…”
Section: Programming Modelmentioning
confidence: 99%
“…This contrast with the way CPU application code needs alterations in algorithm and syntax when ported to a GPU using CUDA. An application written for the MIC architecture using the Intel C or Vector Pascal compilers runs unaltered not only on the Xeon Phi, but also on computers with standard Intel processors [29].…”
Section: Mic Architecture (Intel Xeon Phi Coprocessors)mentioning
confidence: 99%